2003
DOI: 10.1159/000074166
|View full text |Cite
|
Sign up to set email alerts
|

The donor chromosome breakpoint for a jumping translocation is associated with large low-copy repeats in 21q21.3

Abstract: Jumping translocations (JTs) are very rare chromosome aberrations, usually identified in tumors. We report a constitutional JT between donor chromosome 21q21.3→qter and recipients 13qter and 18qter, resulting in an ∼15.5-Mb proximal deletion 21q in a girl with mild developmental delay and minor dysmorphic features. Using fluorescence in situ hybridization (FISH) studies, we identified an ∼550-kb complex inter- and intra-chromosomal low-copy repeat (LCR) adjacent to the 21q21.3 translocation breakpoint. On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…Many of these JTs were positive for interstitial telomere sequences. Stankiewicz et al [2003] studied a JT in a girl with mental retardation and showed that the 21q21.3 donor site was in a low copy repeats (LCR).…”
Section: Postnatalmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of these JTs were positive for interstitial telomere sequences. Stankiewicz et al [2003] studied a JT in a girl with mental retardation and showed that the 21q21.3 donor site was in a low copy repeats (LCR).…”
Section: Postnatalmentioning
confidence: 99%
“…So the recipient sites were more widely distributed in hematological malignancies than in constitutional JTs. Internal telomere sequences were found in most constitutional JTs studied [Rivera et al, 1990;Park et al, 1992;Rossi et al, 1993;Devriendt et al, 1997;Vermeesch et al, 1997;Jewett et al, 1998;Petit et al, 1998;Reddy and Murphy, 2000;Lefort et al, 2001;Sala et al, 2002;Stankiewicz et al, 2003;Zahed et al, 2004], but not in all JTs in hematological malignancies. It has been suggested that the extended proliferation of cancer cells during the premalignant stage, such as myelodysplasia, results in chromosomal instability due to the loss of telomeric functions.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Again, 22q11 does not seem to contain a telomere-related sequence [Azzalin et al, 1997] to facilitate recombination with a true telomere. Stankiewicz et al [2003] reported a girl with mild developmental delay and minor dysmorphic features caused by a constitutional jumping translocation whereby part of the long arm of chromosome 21 (21q21.3 ! ter) was translocated onto 13qter and 18qter with a subsequent 15.5 Mb proximal deletion of chromosome 21.…”
Section: Discussionmentioning
confidence: 99%
“…ter) was translocated onto 13qter and 18qter with a subsequent 15.5 Mb proximal deletion of chromosome 21. The translocation was mediated by an approximately 550-kb complex inter-and intrachromosomal LCR adjacent to the 21q21.3 translocation breakpoint while the telomeric sequence of recipient chromosomes were intact [Stankiewicz et al, 2003].…”
Section: Discussionmentioning
confidence: 99%